Storytelling as a Non-pharmacological Intervention in Dementia: Literature Review - Elita Halimsetiono (Poltekkes Kemenkes Kupang, 2026)
Background: Dementia refers to a group of degenerative diseases of the central nervous system, primarily characterized by impaired cognitive function. Storytelling has the potential to improve cognition, communication, quality of life, psychological well-being, and activities of daily living in people with dementia. Objectives: This article gives a general idea of how storytelling can be used as a non-pharmacological intervention for people with dementia. Methods: This article is a narrative review using the keywords dementia, intervention, and storytelling, which were searched through databases on PubMed and Google Scholar. The inclusion criteria are scientific works published in international journals between 01-01-2017 and 31-01-2026, which are available in full text online. The selection of articles was carried out based on inclusion and exclusion criteria, as well as by paying attention to the title, abstract, and full-text review to see whether it was appropriate to the theme of the article, from which process nine articles were obtained for review. Results: Storytelling fosters productivity, improves cognition and communication, and positively impacts personality, quality of life, and psychological well-being in people with dementia. Storytelling also supports caregiver well-being by reducing stress and distress, and improving the quality of care for people with dementia. Conclusions: Storytelling is a beneficial treatment for people with dementia, their caregivers, and their care environment, so storytelling can be considered as one of the non-pharmacological interventions for dementia.